Improved Embedding of QR Codes onto Surfaces to be 3D Printed. (February 2021) - Papp, György; Hoffmann, Miklós; Papp, Ildikó
Abstract: Providing additional information for parts or items usually means to enclose it next to the object or affix it on the component when that is possible. However, another solution is available by gaining the benefits of an additive manufacturing technology, 3D printing. This technology makes it possible to embed the additional information onto the surface of the items, for example, in the forms of QR codes. In the work of Kikuchi et al. (2018), the QR code is embedded into CAD models that consist of B-spline surfaces by grooving its dark regions to shadow them. The method proposed by Peng et al. (2019) optimized the modules of the QR code and the depth to carve its dark modules into any general mesh. However, embedding the QR code with these methods, in some cases, especially in case of highly curved surfaces, the QR code is deformed during the process of projection onto the surface. This deformation can highly restrict the readability of the QR code. In this paper, we propose an improved method to embed QR codes onto free-form surfaces by using a low-end consumer-level 3D printer. Our aim is to provide a robust method to project the QR code onto surfaces even with high curvature. We discuss the problematic cases for the works mentioned above, and we present a process to find an optimal position and direction of projection for the QR code to avoid deformations on highly curved surfaces. To validate our method, we compare our results with the outcomes of Kikuchi et al. (2018) and Peng et al. (2019). Highlights: Maintain the readability for embedding a QR code on a curved area of free-form surfaces. The usage of central projection for embedding provides a closer reading distance without deformation in the QR code. Patterns in the engraved dark regions of the QR code improve its readability by increasing the contrast between the black and white areas.